Fragmented democracy medicaid, federalism, and unequal politics - Michener, Jamila 1981- (Cambridge University Press, 2018)
"Medicaid is the single largest public health insurer in the United States, covering upwards of 70 million Americans. Crucially, Medicaid is also an intergovernmental program that yokes poverty to federalism: the federal government determines its broad contours, while states have tremendous discretion over how Medicaid is designed and implemented. Where some locales are generous and open handed, others are tight-fisted and punitive. In Fragmented Democracy, Jamila Michener demonstrates the consequences of such disparities for democratic citizenship. Unpacking how federalism transforms Medicaid beneficiaries' interpretations of government and structures their participation in politics, the book examines American democracy from the vantage point(s) of those who are living in or near poverty, (disproportionately) Black or Latino, and reliant on a federated government for vital resources"...